Crystal structure of [meso-5,7,7,12,14,14,-hexamethyl-1,4,8,11-tetraazacyclotetradecane]nickel(II) diperchlorate – dimethylsulphoxide (1/2), C20H48Cl2N4NiO10S2 - Rabi, S.; Dey, L.; Palit, D.; Dey, B. K.; Rahman, Ismail M. M.; Tiekink, Edward R. T. *; Roy, T. G. (De Gruyter Open, 2021)
C20H48Cl2N4NiO10S2, monoclinic, P21/n (no. 14), a = 8.657(2) Å, b = 15.233(4) Å, c = 11.956(3) Å, β = 102.737(2)°, V = 1537.9(7) Å3, Z = 2, R gt (F) = 0.0237, wR ref (F 2) = 0.0655, T = 93(2) K.